Correlations between meaning in life and nature connectedness: German-language validation of two topic-related measures and practical implications - Pfeifer, Eric (Spiritual care, 2024)
Meaning in life and nature connectedness are indicators of a healthy life and correlate with health and well-being. We conducted a validation study of German versions of the Meaning in Life Questionnaire (Steger et al. 2006) and Nature Connection Index (Richardson et al. 2019) and assessed mindfulness as a trait and personality (big five personality traits) among participating students (n = 353). Results indicated a significant positive correlation between nature connectedness and presence of meaning in life. Presence of meaning correlated significantly with less neuroticism, more openness to new experiences, greater conscientiousness, and moderately with the two mindfulness subscales, ‘acceptance’ and ‘presence’. Search for meaning was associated with more neuroticism and less acceptance. A higher nature-connectedness score correlated with more presence and acceptance (mindfulness), greater openness, and less neuroticism (personality traits). Furthermore, we introduce a nature-assisted model of meaning fulfilment that can be applied in healthcare practices, counselling, and (psycho-) therapeutic treatment. Our results contribute to growing evidence on the preventive and curative effects of nature connectedness and meaning in life and their role as health-related resources. Nature connectedness and meaning in life are effective resources considering various aspects related to (global) crises such as climate change and the corona pandemic.